Coaching and Its Effects on Work Motivation and Commitment Among Generation Z - Ukkonen, Emmi (My University, 2026)
Generation Z is the youngest generation entering the workforce, which makes understanding its work-related expectations essential for organizations. This generation is considered distinctive in terms of its values and expectations, which emphasize meaningful work, individuality, and continuous feedback. It is important for organizations to recognize these needs to develop leadership practices that attract and retain young employees. Examining coaching leadership is particularly relevant, as it offers an approach to addressing these changing expectations in a working life where traditional leadership models may no longer be sufficient. This study examines the effects of coaching leadership on work motivation and organizational commitment among Generation Z. The study has been conducted as a qualitative study, and the data have been collected through nine semi structured thematic interviews. The participants represented different industries, and all interviewees belonged to Generation Z. The data have been analysed using qualitative content analysis, through which key themes and meanings related to the relationship between coaching leadership, work motivation, and organizational commitment have been identified. The aim of the study is to examine the significance of coaching leadership specifically in relation to the work motivation and organizational commitment of this generation. The results indicate that the key characteristics of coaching leadership such as supervisor support, regular feedback, individual opportunities for influence, and work life balance form a framework that promotes employees’ autonomy, competence, and sense of belonging. The findings suggest that coaching leadership not only enhances work motivation but also strengthens employees’ experiences of participation and influence. The study highlights that Generation Z particularly values feedback and people-oriented leadership. Coaching leadership emerges as a key factor in meeting these needs. It supports motivation and organizational commitment by strengthening the experience of meaningful work, professional development, and job satisfaction. However, the effects are context dependent and influenced by how leadership practices are implemented within organizations. Overall, the study demonstrates that coaching leadership is part of a broader transformation in working life, where employee centeredness, interaction, individuality, and well-being are increasingly emphasized. Based on the findings, organizations should invest particularly in supervisors’ interaction skills and the development of a feedback culture to meet the expectations of the younger workforce. The continuous transformation of working life requires organizations to adapt to attract, engage, and retain skilled employees in the long term.
Keywords: leadership (activity); work motivation; coaching; generation z; feedback; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development